Pengaruh model pembelajaran discovery learning terintegrasi ayat-ayat Al-Quran terhadap hasil belajar fisika dan sikap spiritual siswa Ponpes Modern As-Sa’adah pada materi gerak melingkar - Haryadi, Rudi; Antarnusa, Ganesha; Apriliyanti, Sherly (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research was conducted to determine the effect of the discovery learning model integrated with verses from the Koran on the physics learning outcomes and spiritual attitudes of As-sa'adah modern Islamic boarding school students on circular motion material, with data collection techniques through pretest and posttest. Purpose sampling technique, the sample consisted of 30 students from the As-sa'adah Modern Islamic Boarding School, Serang Banten. The analytical method used in this research is Quantitative Data Analysis. The research results show that the results of learning physics and spiritual attitudes without using the Discovery Learning learning model integrated with Al-Quran verses, based on the descriptive test, are quite good. Physics learning outcomes and spiritual attitudes using the integrated Discovery Learning learning model of Al-Quran verses, based on descriptive tests in the good category. There is an influence of the Discovery Learning learning model integrated with Al-Quran verses and without integrated Al-Quran verses. The results of the Pretest analysis obtained a p-value= 0.034 and the Posttest obtained a p-value= 0.000. This shows that the p-value (sig) < 0.05, so H0 is rejected. Thus, it can be concluded that student learning outcomes after treatment between the experimental group and the control group are significantly different.